Recent Advances of Nanotechnology-Facilitated Bacteria-Based Drug and Gene Delivery Systems for Cancer Treatment - Chaojie Zhu; Zhiheng Ji; Junkai Ma; Zhijie Ding; Jie Shen; Qiwen Wang (Pharmaceutics, 2021)
Cancer is one of the most devastating and ubiquitous human diseases. Conventional therapies like chemotherapy and radiotherapy are the most widely used cancer treatments. Despite the notable therapeutic improvements that these measures achieve, disappointing therapeutic outcome and cancer reoccurrence commonly following these therapies demonstrate the need for better alternatives. Among them, bacterial therapy has proven to be effective in its intrinsic cancer targeting ability and various therapeutic mechanisms that can be further bolstered by nanotechnology. In this review, we will discuss recent advances of nanotechnology-facilitated bacteria-based drug and gene delivery systems in cancer treatment. Therapeutic mechanisms of these hybrid nanoformulations are highlighted to provide an up-to-date understanding of this emerging field.